Design and synthesis of phenylthiophosphoryl dichloride derivatives and evaluation of their antitumour and anti-inflammatory activities - Chunyun Xu; Na Yang; Haichun Yu; Xiaojing Wang (Frontiers in Chemistry)
Tumours and inflammation are serious risks to human health and are importantly regulated by the gas signalling molecule hydrogen sulphide. In this work, we report the rational design and synthesis of H2S donor molecules based on phenylthiophosphoryl dichloride nuclei and assess their efficacy against tumours and inflammation. We predicted its potential anticancer targets based on network pharmacology and then verified the inhibitory effect of the active compound S11 on the pathway PI3K/AKT by enzyme inhibition and molecular docking assay. In addition, compound S11 exhibited a potent anti-inflammatory effect on macrophages, effectively reducing the levels of inflammatory mediators TNF-α, IL-10 and HO-1. Compound S11 can be used as a new chemical entity for the discovery of new anti-cancer drugs or anti-inflammatory drugs.